2012
DOI: 10.1093/molbev/mss161
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Sequencing of Plasmodium falciparum Malaria Parasites from Senegal Reveals the Demographic History of the Population

Abstract: Malaria is a deadly disease that causes nearly one million deaths each year. To develop methods to control and eradicate malaria, it is important to understand the genetic basis of Plasmodium falciparum adaptations to antimalarial treatments and the human immune system while taking into account its demographic history. To study the demographic history and identify genes under selection more efficiently, we sequenced the complete genomes of 25 culture-adapted P. falciparum isolates from three sites in Senegal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
57
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 57 publications
(70 reference statements)
13
57
1
Order By: Relevance
“…Similar to previous studies of directional selection in P. falciparum, we identified drug-resistance genes (e.g., pfcrt and kelch K13) with evidence of strong directional selection (Table 3) (26)(27)(28)(29). Allele frequencies for all polymorphisms in known drugresistance genes are summarized in Table S6.…”
Section: P Vivax Shows Stronger Evidence Of Recent Directional Selecsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar to previous studies of directional selection in P. falciparum, we identified drug-resistance genes (e.g., pfcrt and kelch K13) with evidence of strong directional selection (Table 3) (26)(27)(28)(29). Allele frequencies for all polymorphisms in known drugresistance genes are summarized in Table S6.…”
Section: P Vivax Shows Stronger Evidence Of Recent Directional Selecsupporting
confidence: 76%
“…Inferred parameters for the best-fit one-population demographic scenario for the P. falciparum ancestral-like population, the entire P. vivax population, and the P. vivax monoclonal population were used to parameterize coalescent simulations. Mutation rates per gene were determined from gene length and the calculated genome mutation rate, because the mutation rate per gene considered in the ms model is proportional to gene length (26). From these simulations, we established a null distribution of Tajima's D values for both P. vivax populations and for the P. falciparum ancestral-like population to aid in identifying genes under unexpectedly strong balancing or directional selection.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study based on only 25 parasite isolates, we observed two unusual patterns in the P. falciparum genome that had not been reported in any other organism (4). First, we observed synonymous and nonsynonymous site-frequency spectra that were more similar than expected, given that nonsynonymous sites likely experience stronger selection.…”
supporting
confidence: 45%
“…M alaria, which is caused by the parasite Plasmodium falciparum, is one of the major causes of death worldwide. To aid the development of vaccines and drug treatments for malaria, researchers have studied the P. falciparum genome and identified genes that are essential to malaria parasites as well as genes that are related to drug-resistance phenotypes using population genetic tools (1)(2)(3)(4)(5)(6). Researchers have also focused on particular genes related to drug resistance and characterized the evolutionary pathways of emerging drug resistance using Escherichia coli and Saccharomyces cerevisiae as model systems (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Additionally, recent analysis of genome-wide Single Nucleotide Polymorphisms (SNPs) in P. falciparum had indicated population structure among continents, with no signature of population sub-structuring in Africa (Manske et al, 2012). A very similar study with genome-wide SNPs of P. falciparum populations from Senegal (Africa) have corroborated the above finding, as no significant population structure could be detected in Senegal (Chang et al, 2012). In contrast, the Southeast Asian P. falciparum populations were found to be significantly structured based on SNP (Manske et al, 2012) and also in microsatellite markers (Pumpaibool et al, 2009).…”
Section: Introductionmentioning
confidence: 75%